PENERAPAN METODE PENEMUAN TERBIMBING UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS VII SMP NEGERI 6 PALU PADA MATERI HUBUNGAN SUDUT-DALAM DAN SUDUT-LUAR SEGITIGA - Aminudin, Rusmin (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
The purpose of this research aim to the describe of applying the guided discovery method in improving the understanding of student in class VII Junior High School 6 Palu of relation interior-angle trilateral and external-angle. This Research type is class action research. Research device relate at model of Kemmis and Mc Taggart executed with two cycle. Result of research indicate that the applying of guided discovery method can improve the understanding of student in class of VII Junior High School 6 Palu in items of relation of interior-angle and trilateral external-angle with the characteristic that is: (1) lesson items presented in the form of problem, (2) concept and formula taught to pass the activity in LKS, (3) teacher of personating fasilitator in course of study, (4) interaction in class have the character of the multi instruct.